Mucinous Adenocarcinoma of Skin Annex: a Case Report - Moura, Karolinny Borinelli de Aquino (2013)
Introduction: The mucinous adenocarcinoma is a rare neoplasm composed of apocrine skin cells that produce mucus. Eyelids, scalp and other regions of the head and neck are the most primary sites affected. Case report: The authors describe a suspicious lesion in the scalp, whose excision and analysis confirmed a mucinous adenocarcinoma of Skin Annex. Even after resection, there were metastatic lesions in these regions: retroauricular, cervical, supraclavicular and scalp. Thus, she went under chemotherapy and radiotherapy. Months later, the patient reported back pain radiating to the arm, hands and paresthesias. After examination, metastases have been confirmed on axillary lymph nodes, bones of the spine, with imminent spinal cord compression. Then, radiation therapy was done in these regions. The patient has improved significantly and, nowadays, she keeps monitoring it. Conclusion: The mucinous adenocarcinoma is a rare neoplasm and the characteristics of this reported case makes it even rarer. The diagnosis requires clinical, radiological and pathological correlation. When the patients are submitted to early treatment, they have a good prognosis with few chances of metastases, although recurrences are common.